De Exu a Ñande ru: o ensino de filosofia e a lei nº 11.645/08 - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present paper focuses on investigating the possibility of the applicability of the federal law No. 11.645, promulgated on March 10 of 2008, in the teaching of philosophy in high school years. Reflecting on which ways the teaching of counterhegemonic knowledge of African origin, of Native Peoples and of Afrodiaspora can be articulated with the teaching of philosophy, especially with its critical sieve of promoting the exercise of full and responsible citizenship of the students. The traced objectives were to analyze the philosophical contents from the basis of the specific competences of the humanities area presented in the Common National Curriculum Base in relation to the horizon of African and Latin American philosophies. Likewise, it was sought to identify the interfaces with the contents of philosophy in the law 11.645/2008. Still, indicating theoretical and methodological possibilities of philosophy teaching in the scope of decolonial theories. Having an experimental methodology through bibliographical research starting from concepts such as Afroperspectivity, the pedagogy of the crossroads and the philosophy of liberation. As a result, perceptions were obtained on the paths that point to possibilities for the applicability of the law on the teaching of African, Afro-Brazilian and Indigenous History and Culture in the teaching of philosophy in high school from the knowledge of the sphere of decolonial thinking.
Keywords: Filosofia - Estudo e ensino; Ensino - Legislação; Cultura afro-brasileira; Indígenas - Usos e costumes; Ensino médio; Philosophy - Study and teaching; Teaching - Legislation; CNPQ::CIENCIAS HUMANAS